L’ image des femmes libyennes dans le livre IV des "Histoires" d’Hérodote - Diouf, Benjamin (Res antiquae, 2022)
The Greek historian Herodotus left some interesting and well-researched information about Libyan women during classical antiquity. But the work carried out on the lifestyles of these women often does not allow us to fully understand their customs and identify their roles in their societies. The present study fills these gaps by providing valuable insights into the customs of these former Libyan women, which can be considered as their legacy to certain ethnic groups still living in Libya, a legacy similar to that of other African populations.